CO and CO2 Methanation Over Ni/SiC and Ni/SiO2 Catalysts - Le, Thien An; Kang, Jong Kyu; Park, Eun Duck (Topics in Catalysis, 2018)
Ni/SiC and Ni/SiO2 catalysts prepared by both wet impregnation (WI) and deposition–precipitation (DP) methods were compared for CO and CO2 methanation. The prepared catalysts were characterized using N2 physisorption, temperature-programmed reduction with H2 (H2-TPR), H2 chemisorption, pulsed CO2 chemisorption, temperature-programmed desorption of CO2 (CO2-TPD), transmission electron microscopy, and X-ray diffraction. H2-TPR analysis revealed that the catalysts prepared by DP exhibit stronger interaction between the nickel oxides and support than those prepared by WI. The former catalysts exhibit higher Ni dispersions than the latter. The catalytic activities for both reactions over Ni/SiC and Ni/SiO2 catalysts prepared by WI increase on increasing the Ni content from 10 to 20 wt%. The Ni/SiC catalyst prepared by DP shows higher catalytic activity for CO and CO2 methanation than that of the Ni/SiC catalyst prepared by WI. Furthermore, it exhibits the highest catalytic activity for CO methanation among the tested catalysts. The high Ni dispersion achieved by the DP method and the high thermal conductivity enabled by SiC are beneficial for both CO and CO2 methanation.
Keywords: Co methanation; H2 chemisorption; High thermal conductivity; Ni/SiO2; Ni/SiO2 catalysts; Precipitation methods; Temperature-programmed reduction; Wet impregnation; CO methanation; CO2 methanation; Deposition–precipitation method; Ni/SiC; Ni/SiO2